Toxin-Antitoxin Systems in the Mobile Genome of Acidithiobacillus Ferrooxidans - Tello-Reyes, M (Public Library of Science, 2014)
Toxin-antitoxin (TA) systems are genetic modules composed of a pair of genes encoding a stable toxin and an unstable antitoxin that inhibits toxin activity. They are widespread among plasmids and chromosomes of bacteria and archaea. TA systems are known to be involved in the stabilization of plasmids but there is no consensus about the function of chromosomal TA systems. To shed light on the role of chromosomally encoded TA systems we analyzed the distribution and functionality of type II TA systems in the chromosome of two strains from Acidithiobacillus ferrooxidans (ATCC 23270 and 53993), a Gram-negative, acidophilic, environmental bacterium that participates in the bioleaching of minerals. As in other environmental microorganisms, A. ferrooxidans has a high content of TA systems (28-29) and in twenty of them the toxin is a putative ribonuclease. According to the genetic context, some of these systems are encoded near or within mobile genetic elements. Although most TA systems are shared by both strains, four of them, which are encoded in the active mobile element ICEAfe1, are exclusive to the type strain ATCC 23270. We demostrated that two TA systems from ICEAfe1 are functional in E. coli cells, since the toxins inhibit growth and the antitoxins counteract the effect of their cognate toxins. All the toxins from ICE Afe1, including a novel toxin, are RNases with different ion requirements. The data indicate that some of the chromosomally encoded TA systems are actually part of the A. ferrooxidans mobile genome and we propose that could be involved in the maintenance of these integrated mobile genetic elements. Copyright © 2014 Bustamante et al.